EFFICACY OF ETANERCEPT IN TREATMENT OF VARIOUS TYPES OF JUVENILE IDIOPATHIC ARTHRITIS - O. Yu. Konopel'ko; E. S. Zholobova; M. N. Nikolaeva; O. S. Rozvadovskaya; V. Ya. El'yashevich; E. Yu. Afonina (Вопросы современной педиатрии)
Aim: to assess efficacy and safety of etanercept in treatment of various types of juvenile idiopathic arthritis in children under conditions of real clinical practice. Patients and methods: 52 children were included into the study, among them 16 were with systemic and 36 with juvenile idiopathic arthritis without extra-articular involvement. Results: etanercept treatment was the most efficient in patients with systemic juvenile idiopathic arthritis without extra-articular involvement. In 6 and 12 months of the treatment 50 and 70% improvement according to the ACRpedi criteria were established in 31/36 (86%) and 28/36 (78%) of the patients, respectively. In 24 months in 5 (29%) of 17 children remained in the study remission stage of the diseases was confirmed. Conclusions: etanercept treatment was not associated with significant unfavorable effects, which allows to recommend this drug for treatment of juvenile idiopathic arthritis without extra-articular involvent and resistant to standard anti-rheumatic therapy.